Utilization of artificial intelligence approach for prediction of DLP values for abdominal CT scans: A high accuracy estimation for risk assessment - Tekin, H. O.; Almisned, Faisal; Erguzel, T. T.; Abuzaid, Mohamed M.; Elshami, W.; Ene, Antoaneta; Issa, Shams A. M.; Zakaly, Hesham M. H. (Frontiers in Public Health, 2022)
Purpose: This study aimed to evaluate Artificial Neural Network (ANN) modelling to estimate the significant dose length product (DLP) value during the abdominal CT examinations for quality assurance in a retrospective, cross-sectional study. Methods: The structure of ANN model was designed considering various input parameters, namely patient weight, patient size, body mass index, mean CTDI volume, scanning length, kVp, mAs, exposure time per rotation and pitch factor. The aforementioned examination details of 551 abdominal CT scan were used as retrospective data. Different types of learning algorithms such as Levenberg-Marquardt, Bayesian and Scaled-Conjugate Gradient were checked in terms of the accuracy of the training data. Results: The R-value was representing the correlation coefficient for the real system and system output is given as 0.925, 0.785 and 0.854 for the Levenberg-Marquardt, Bayesian and Scaled-Conjugate Gradient algorithms, respectively. The findings showed that the Levenberg-Marquardt algorithm comprehensively detect DLP values for abdominal CT examinations. It can be a helpful approach to simplify CT quality assurance. Conclusion: It can be concluded that outcomes of this novel artificial intelligence method can be used for high accuracy DLP estimations before the abdominal CT examinations, where the radiation-related risk factors high or risk evaluation of multiple CT scans are needed for patients in terms of ALARA. Likewise, it can be concluded that artificial learning methods are powerful tools and can be used for different types of radiation-related risk assessments for quality assurance in diagnostic radiology.